A study on estimation of time since death after histological examination of kidney - Thakur, Rajani; Goyal, M.; Bhawnani, Dhiraj (International Journal of Research in Medical Sciences, 2017)
Background: Estimation of time since death is one of the most important object of post-mortem examination. Many degenerative changes begin to take place in the body immediately or shortly after death. Kidney is one of the most important excretory organs of human body, its undergo series of gross as well as histological changes. Methods: This study was performed in department of anatomy in close association with the department of forensic medicine & toxicology and pathology, Pt. J. N. M. medical college and DBRAM hospital Raipur (C.G.) India, during study period November 2012 to October 2013. Study was done on 50 human cadavers (Study subjects). Kidney was obtained from dead bodies during post-mortem examination. In each case kidney was studied histologically. Data was compiled in MS excel and checked for its completeness and correctness and then it was analyzed. Results: In 48-60 hour increasing temperature, one case show very severe change was seen. Microscopic changes in kidney were increasing (mild to moderate, moderate to severe, severe to very severe) as temperature increases. Conclusion: In the present study earliest remarkable postmortem histological changes were seen in DCT. Finding of present study will be useful for forensic experts.